Cryo-Electron Microscopy Studies of Biomolecular Structure and Dynamics - Arkadiusz W. Kulczyk (Micromachines)
The technical innovation of the last decade has provided novel tools that are now transforming the field of biophysics by bringing remarkable atomic level insights into the mechanisms employed by bio-micromachines to sustain life [...]